IMPLEMENTASI PEMBELAJARAN TEKS CERITA FANTASI DI SMPN 2 MENUKUNG KABUPATEN MELAWI - Sari, Shinta Novita; Martono, Martono; Syam, Christanto Syam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research is a research to see how the implementation of learning fantasy story texts for class VII students at SMP N 2 Menukung, Melawi Regency. The problems examined in this study were regarding the planning, implementation, and results of the assessment of fantasy story text learning in class VII SMP N 2 Menukung. The purpose of this study is to describe the planning, implementation, and assessment of learning fantasy story text in class VII SMP N 2 Menukung. The method used is a descriptive method with a form of research is a form of qualitative research. The data in this study came from class VII Indonesian teachers. Based on the analysis that has been done with the formulation of the problem that has been made. First, in this lesson plan the lesson plan made by the teacher meets the standards because there are introductions, core activities, and closing learning activities which are components of the lesson plans. Second, the implementation of learning, during the implementation of the learning process is quite interesting and fun. However, the media used is limited because it only depends on the textbooks provided by the school. Third, the assessment of learning is quite satisfactory and there are some students in learning fantasy story texts who really have to be guided regularly and structured so that the expected learning objectives are achieved properly.